Lo sublime apofático y la estética neoplatónica - Papoulias, Haris (2025)
The intersection between the idea of the sublime in Greek aesthetics and poetics and Neoplatonic thought at the end of Antiquity and the beginning of the Byzantine period is an important field of work yet to be investigated. This study seems to us fundamental to understand the foundations of the visual and conceptual turn that occurs between the fourth and seventh centuries in the field of philosophy of the arts and Late Antique Greek poetry, in an era marked by philosophical and aesthetic – and soon religious and political – discussion about images, their power, their representativeness and their ontological status. On this unexplored field, the present contribution aims to outline a preliminary methodology and a first approach to what we have come to call “the apophatic sublime”, as a new incipient category of study that can help to open a new way for a better understanding, at the same time, of the developments of Neoplatonic aesthetics and of the authors of Christian and pagan poetry of this period.